Production cost models with regard to liberalised electricity markets - Martinez Diaz, David José (KIT Scientific Publishing, 2008)
This book makes a contribution to the formulation and implementation of production cost models for the modelling of liberalized electricity markets by addressing issues associated with the level of detail in the representation of the underlying power system, the accuracy of the results and the modelling effort. To this end a production cost model was formulated and applied to estimate the short-run marginal cost of the power systems of three important European electricity markets.